Model of Increasing Employee Productivity at PT. Primafood International - Ahmad Waruwu; Slamet Widodo; Suhendi; Edni Marchelli (Penerbit Jurnal Indonesia, 2024)
Human resource capabilities are a key factor in increasing employee work productivity, so research needs to be carried out. The aim of this research is to find out whether work workload and work stress partially have a positive and significant effect on work productivity at PT. Primafood International. To find out whether Workload and Work Stress simultaneously have a positive and significant effect on Work Productivity at PT. Primafood International. The analysis technique used in this research is quantitative data analysis, namely testing and analyzing data by calculating numbers and then drawing conclusions from the test using descriptive statistical and correlation test tools, data processing using SPSS statistical software. From the partial research results, there is no influence of workload on employee work productivity at PT. Primafood International. There is a positive and significant influence of work stress on employee work productivity at PT. Primafood International. There is a positive and significant influence of work workload and work stress on product work productivity at PT. Primafood International.